PENGEMBANGAN VIDEO ANIMASI 3D BERBASIS AI SEBAGAI MEDIA PEMBELAJARAN MATERI PECAHAN SENILAI PADA KELAS IV GUNA MENDUKUNG INOVASI GURU DAN MINAT BELAJAR SISWA - Anis Thasia; Raden Wisnu Wijaya Dewojati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The purpose of this study is to develop a 3D animated video media based on Artificial Intelligence (AI) on the topic of equivalent fractions for fourth-grade elementary school students. This research is motivated by students' low understanding of the abstract concept of fractions and the limited use of innovative learning media. The method used in this study is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects consisted of three experts, one teacher, and 11 fourth-grade students at SD Negeri 8 Simpang Pesak. Data collection techniques used observation, interviews, and questionnaires, while data analysis was carried out qualitatively and quantitatively. The results showed that the media obtained an expert validation score of 87.33% with a "very good" category. At the implementation stage, teacher and student responses each reached 100% with a "very good" category. The overall average of 95.77% indicates that the developed media is not only feasible but also very practical to use in learning. Thus, AI-based 3D animated video media is effectively used to help increase teacher innovation and student learning interest in equivalent fractions material.